Decisive Use of Building Materials Based on Hygrothermal Analysis. (June 2019) - Brauner, M; Ghaffarianhoseini, A; Naismith, N; Tookey, J
Abstract: Sustainable buildings, planning and construction process in the 21st century require an interdisciplinary approach by which the use of materials and products has to be a result of a complex decision procedure. Every building in its life span has an immense impact on the environment. This study shows that even small changes in material specification can engender a significant influence on indoor air quality and the whole ecosystem. This paper represents the second part of a research study described and presented by the CESB16 conference. An experimental and numerical study on real houses delivers new data which demonstrate the importance of material determination during the design process. Four different scenarios have been tested in two houses while introducing water vapour into a room to simulate occupancy. Indoor relative humidity, temperature and absolute humidity in the same room (size, position in the house, orientation) have been monitored while introducing various materials with a divergent moisture buffering capacity. This research has been based on real measurements assessed the data and compared with the hygrothermal performance of the original construction. The study further used a hygrothermal simulation to demonstrate the possibility of early materials assessment and allowance for the targeted specification of building materials. The information on how to efficiently use the hygrothermal qualities of materials in a build environment is a contribution to the goal of designing and constructing sustainable buildings.